Пролетарский интернационализм и мелкобуржуазный национализм - Кюзаджян Липарит Саркисович (Политиздат, 1968)
Экземпляры: КХ (20210809) / Инвентарный номер: 0185973 / Сис.шифр: 323.1 / Авт.знак: К 99 / ГРНТИ: 11 / ББК: 87